Juridical Implications on Agreements Using Back Date Made in The Form Uthentic Deed by Notary - Anggraini, Lia Ayu (Journal of Law, Politic and Humanities, 2025)
A backdated agreement is created to cover certain activities that are not actually included in a contract. For example, in the early stages of implementing a project or cooperation based on trust without a previously drafted contract, both parties then realize that the cooperation needs to be further explained in a contract. Therefore, they draft the contract with a backdated date to the time when the work first began. An agreement drafted with a backdated date is basically still based on the ratification of all parties involved, so it does not cause any harm to them. However, it is important to note that differences in signing dates can have a negative impact on other parties who may not be directly involved in the agreement. This situation occurs because an agreement signed with a backdated date can be considered as a document forgery treatment. The method of research employed in this study is normative juridical, encompassing a legal-based approach, case analysis, and a conceptual approach. The findings of this research suggest that contracts with backdated dates and executed through a notary deed are legally acknowledged, but they do not hold the same legal weight as an authentic deed. Therefore, the contract is deemed valid and binding for all parties, with the guarantee structured in line with the stipulations outlined for the agreement's validity (as per Article 1320 of the Civil Code). Additionally, the legal implications of employing a backdated contract in the form of an authentic deed result in a downgrade in its status, transitioning it from authentic to private deed. Consequently, the verifying power previously held by the authentic deed, which was once robust in civil court proceedings, diminishes to the level of a private deed, rendering its evidentiary power ineffective.